Clinical and Radiological Predictors of Functional Outcome After Isolated Medial Patellofemoral Ligament Reconstruction at Midterm Follow-up. Issue 6 (May 2019) - Neri, Thomas; Parker, David Anthony; Putnis, Sven; Klasan, Antonio; Trombert-Paviot, Beatrice; Farizon, Frederic; Philippot, Remi
Background: Isolated medial patellofemoral ligament reconstruction (iMPFLR) is increasingly used for the surgical treatment of recurrent patellofemoral instability. Purpose: The purpose of this study was to identify the clinical and radiological predictors that can significantly influence the functional outcomes after an iMPFLR. Study Design: Case series; Level of evidence, 4. Methods: A total of 107 patients (112 ligament reconstructions) who underwent iMPFLR were evaluated with a mean ± SD follow-up of 59 ± 33 months (range, 12-123 months). Functional International Knee Documentation Committee (IKDC) and Kujala scores were assessed preoperatively and every 12 months. Radiological assessment of patellar height and tilt (Laurin angle, Merchant angle, Maldague classification) and computed tomography (CT) scan measurement of patellar tilt (contracted and relaxed quadriceps) and tibial tubercle–trochlear groove distance were performed preoperatively and at 6 months. Femoral tunnel position was assessed following the criteria formulated by Schöttle. The amount of femoral tunnel widening was measured by means of 3-dimensional CT scan at 6 months. Predictors were determined from univariate and multivariate regression analyses integrating clinical and radiological criteria pre- and postoperatively. The dependent variable was defined as the difference between pre- and postoperative scores. Results: Between pre- and postoperative measurement at last follow-up, a significant improvement for IKDC and Kujala functional scores was observed (Kujala: 57 ± 11.3 to 87 ± 12.9, P < .001; IKDC: 47.8 ± 13.1 to 79 ± 15.8, P < .001). Demographics (age, body mass index, sex), dislocation characteristics (number of dislocations, time between first dislocation and surgery, age at first dislocation, mechanism of first dislocation, knee side), clinical data (frontal limb alignment, hyperlaxity, recurvatum, pre- and postoperative range of motion), and complications (quadriceps atrophy, complex regional pain syndrome) did not influence functional scores. The predictors of lower improvement in functional scores included small correction of the patellar tilt reported on the CT scan measurement, malpositioning of the femoral tunnel, and a widening of this tunnel near the medial cortex. Malpositioning of the femoral tunnel was correlated with tunnel widening, and patients with anterior and proximal malpositioning experienced stiffness in flexion. Conclusion: Overall, iMPFLR demonstrated good outcomes. Predictors influencing the functional results were identified. Less improvement in clinical outcome was reported for patients with a high preoperative patellar tilt and only a small correction in tilt and for those who had femoral tunnel malpositioning, which was correlated with tunnel widening.